Hubungan Konsumsi Gula dan Derajat Keparahan Dismenore Primer pada Siswi Madrasah Aliyah Pembangunan UIN Syarif Hidayatullah Jakarta - Raihan Putri Sakiinah; Francisca A. Tjakradidjadja; Muniroh Muniroh (Universitas Pahlawan Tuanku Tambusai, 2026)
One of the risk factors for primary dysmenorrhea in adolescent girls is excessive sugar consumption. There are inconsistencies regarding the correlation between sugar consumption and the severity of primary dysmenorrhea in previous studies. This study aims to determine the correlation between sugar consumption and the severity of primary dysmenorrhea among students of MA Pembangunan UIN Jakarta. An analytical observational study using a cross-sectional method was conducted on 53 students of the MA Pembangunan UIN Jakarta. The analysis using the Kolmogorov-Smirnov test showed no significant relationship between sugar consumption frequency (p-value = 0.692, p>0.05) and daily sugar consumption levels (p-value = 0.782, p>0.05) with the severity of primary dysmenorrhea among students of MA Pembangunan UIN Jakarta. The conclusion of this study is no significant correlation between sugar consumption and the severity of primary dysmenorrhea among students of MA Pembangunan UIN Syarif Hidayatullah Jakarta. Keywords: Sugar Consumption, Primary Dysmenorrhea, Students of Madrasah Aliyah.